Critical digital literacy strategies for the promotion of reading comprehension in the classrooms (2021)
The purpose of this research is to determine which are the critical digital literacy strategies used by teachers of the foreign language program of a private university, to promote critical reading comprehension competence in their students when carrying out and putting into practice different activities that integrate the use of technology, and to determine whether these activities allow students to develop reading comprehension skills through critical digital literacy or not. From there, we aim to recognize if educators are trained to face this new phase of a digitized education, if their critical digital literacy strategies developed in class are effective for the promotion of critical and reflective students, capable of investigating and sharing different opinions when they are exploring digital texts. Through this research it is intended to present others carried out by different academics who have knowledge in the research in question, in order to have theoretical support related to reading comprehension, critical digital literacy and the different strategies used in their promotion. In which we found that professors need to learn more about digital literacy and that they all implement different strategies to improve students’ reading comprehension skills.